2002
DOI: 10.1111/j.1549-0831.2002.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Inequality in Homeownership: Does Place Make a Difference?*

Abstract: Racial differences in homeownership have long been a topic of sociological study. Previous studies, however, neglected to consider differences in levels of homeownership between nonmarried black and white women in the context of place. Accordingly this paper focuses on the interaction between place, race, and gender and its impact on homeownership for nonmarried persons. The study employs the Integrated Public Use Microdata Series (IPUMS) and logistic regression analysis to address the following questions: Has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In this achievement-oriented lending environment, lenders may value high status qualities of agency and self-reliance; therefore, the intersectional invisibility accorded to black women may be advantageous. Few studies have examined the combined effect of gender and race on lending decisions, as previously discussed, though the results tend to align with intersectional invisibility predictions (Allen 2002;Robinson 2002). This study provides an additional test of this hypothesis.…”
Section: Status Evaluations and Intersectionalitysupporting
confidence: 61%
See 1 more Smart Citation
“…In this achievement-oriented lending environment, lenders may value high status qualities of agency and self-reliance; therefore, the intersectional invisibility accorded to black women may be advantageous. Few studies have examined the combined effect of gender and race on lending decisions, as previously discussed, though the results tend to align with intersectional invisibility predictions (Allen 2002;Robinson 2002). This study provides an additional test of this hypothesis.…”
Section: Status Evaluations and Intersectionalitysupporting
confidence: 61%
“…Additionally, the extant research examining lending decisions generally has focused only on the singular effects of race or gender. In a notable exception, Allen (2002) documents that from 1970 to 1990, rates of homeownership for single black women increased steadily in rural areas such that the racial gap in nonmarried female homeownership began to close by the end of that twenty-year period. Furthermore, Robinson’s (2002) analysis of the 1992 Boston Federal Reserve study of mortgage lending revealed that white married couples experienced mortgage discrimination if the wife was the sole breadwinner.…”
mentioning
confidence: 99%
“…Religious values and behaviors also potentially influence family formation and marital instability (Wilcox & Wolfinger, ) as well as the wealth accumulation process (Keister, ). Geographic variation in homeownership and housing values may also affect the wealth accumulation of older women, especially among Black women, who are overrepresented in the South and in central cities (Allen, ; Woldoff & Ovadia, ). Last, familial obligations and household size, measured by the number of children born, is expected to influence wealth accumulation and savings behavior (Chiteji & Hamilton, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Levin, 2014;Tester, 2008), although the intersection specifically of parental-tenure and migrant status has not been considered. But quantitative studies of homeownership have tended to elide questions of intersectionality (see Allen (2002) for an exception). Certainly, this is true of quantitative studies of homeownership patterns concerned with migrant or parental-tenure status.…”
Section: Key Open Questionsmentioning
confidence: 99%